PENGARUH VOLUME PERDAGANGAN DAN FREKUENSI PERDAGANGAN TERHADAP RETURN SAHAM PADA PT. AKASHA WIRA INTERNATIONAL, TBK TAHUN 2023 - Gea Rosnani Saragih; Eja Armaz Hardi; Rohana Rohana (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to determine the effect of trading volume and trading frequency on stock returns at PT. Akasha Wira International, Tbk 2023. This research uses a quantitative approach with the data collection method obtained is secondary data, the population in this research is daily data on trading volume and trading frequency. The sample in this research uses a saturated sample. The results of this research show that the trading volume variable influences stock returns individually with a significance level of 0.001. Trading frequency has no effect on stock returns with a significant value of 0.415. Meanwhile, together, trading volume and trading frequency influence stock returns with a significant value of 0.001.